Studi Partisipasi Pria dalam Program Keluarga Berencana di Kecamatan Tugu Kota Semarang - Yustianingsih, Yustianingsih; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2014)
Indonesia is a developing country with one of the problems is large population growth. To reduce the rate of population growth, the government launched a Family Planning Program. Family Planning Program is a movement to establish a healthy and prosperous families by limiting births. For the success of family planning programs need a community participation, especially the participation of male. This research was conducted in the District of Tugu, Semarang City, using qualitative-descriptive methods. This study aims to description male participation in family planning programs in District of Tugu and identify the factors that inhibit the participation of male in family planning programs in District of Tugu. Collecting data in this study using interviews with informants and by observation. To describe the participation of male in family planning programs, using the theory of the participation of Keith Davis, there is also a theory of communication and education are used to determine what might be inhibiting male participation. From the research, it was found that male participation in family planning programs in District of Tugu is still relatively low. There are factors that hinder the participation of male in family planning programs in District of Tugu that is a factor of communication and education.